2014
DOI: 10.1002/2013jd021291
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional leader development in sprite‐producing positive cloud‐to‐ground flashes: Origins and characteristics of positive and negative leaders

Abstract: Thirty-five sprite-producing lightning flashes were recorded in nine nights in different seasons at the east coast of Spain with a 3D Lightning Mapping Array (LMA) since July 2011. A low-frequency time-of-arrival network provided data on emissions from return strokes and intracloud processes and a very-high-frequency interferometer network produced complementary lightning data. This study analyzes the bidirectional development of flashes in order to understand the positioning and timing of the positive cloud-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
50
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 73 publications
9
50
0
Order By: Relevance
“…Yet this does not always appear to be the case with some reports in the literature of negative GJs occurring during the later stages of a thunderstorm's life cycle [e.g., Soula et al, 2011;Meyer et al, 2013]. Under these circumstances, it is possible that upper level shear may also play a role by enhancing the mixing at storm top or by differentially advecting the upper charge region downstream of the main central charge [van der Velde et al, 2010]. However, it is thought that the latter would tend to promote IC flashes within the anvil region rather than produce a jet or GJ [Riousset et al, 2010].…”
Section: 1002/2015jd023383mentioning
confidence: 95%
See 2 more Smart Citations
“…Yet this does not always appear to be the case with some reports in the literature of negative GJs occurring during the later stages of a thunderstorm's life cycle [e.g., Soula et al, 2011;Meyer et al, 2013]. Under these circumstances, it is possible that upper level shear may also play a role by enhancing the mixing at storm top or by differentially advecting the upper charge region downstream of the main central charge [van der Velde et al, 2010]. However, it is thought that the latter would tend to promote IC flashes within the anvil region rather than produce a jet or GJ [Riousset et al, 2010].…”
Section: 1002/2015jd023383mentioning
confidence: 95%
“…Both of these tropical systems had low-level jet-like (LLJ) features associated with them [McCaul, 1987]. Three separate oceanic cases (not included Tables 3-5) were also recorded near the island of San Andrés, Columbia [van der Velde et al, 2014b]. These include a single GJ at 0205 UTC on 23 December 2011, another isolated GJ at 0920 UTC on 12 September 2013, and three GJs between 0846 and 0943 UTC on 18 September 2013.…”
Section: à2mentioning
confidence: 99%
See 1 more Smart Citation
“…These flashes supposedly follow trajectories of charged ice particles toward the stratiform region of the storm system [19,20]. Some of these flashes can be considered as spider lightning [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these flashes can be considered as spider lightning [21,22]. In a recent work [20] the authors identified different modes of evolution of the negative leaders throughout the thundercloud system that can explain the positioning and timing of the positive +CG strokes. Thus, the negative leaders may propagate at various altitudes with different velocities and over various distances, while generating several multiple +CG strokes.…”
Section: Introductionmentioning
confidence: 99%